A constructivist approach to student development: Effat University case study. (1st January 2011) - Ibrahim, Rania; Sarirete, Akila
Sustainable education requires a new approach to knowledge acquisition and learning. This approach is manifested in merging student experience inside and outside the classroom, which eventually results in shaping the 21st century lifelong learner. This paper presents an innovative student development model based on the constructivist approach; showing the collaboration between student affairs and academics. Furthermore, it illustrates a unique experience implemented at Effat University for developing the student as a whole person. This is done to complement the student's academic experience with the necessary skills and abilities derived from Effat University mission that focuses on creating women leaders. The student finds herself in a journey of self development and growth throughout the course of her study until graduation. At the time of graduation, she is equipped with all what it takes to be a successful career woman and a leader of change in her society.